The Effect of Firm Size, Profitability, Leverage, and Financial Distress on Voluntary Disclosure in Annual Report - Menik Indrati; Sherina Oktaviana Aulia (GoAcademica Research & Publishing, 2022)
The purpose of this study is to figure out the effect of firm size, profitability, leverage, and financial distress on voluntary disclosure in company’s annual financial report. This study consists of one dependent variable which is voluntary disclosure and four independent variables which are firm size measured by natural logarithm (Ln) on total assets, profitability measured by Return on Assets (ROA), leverage measured by Debt to Equity Ratio (DER), and financial distress measured by Interest Coverage Ratio (ICR). The research data has 21 companies with the object of consumer goods industrial companies listed on Indonesia Stock Exchange (IDX) during period 2018-2020, so the research are 21 companies with 63 data samples. This study uses multiple linear regression analysis method, and uses the application of the Statistical Program for Social Science (SPSS). The result of this study is firm size, profitability, leverage, and financial distress have a simultaneous effect on voluntary disclosure of annual report. The result of t-test (partially) showed that firm size has a positive significant effects on the voluntary disclosure, profitability has a positive significant effects on the voluntary disclosure, leverage has no significant effect on the voluntary disclosure, and financial distress partially has a negative significant effects on voluntary disclosure.